Loop-free verification of termination of derivation for a fragment of dynamic logic - Pliuškevičius , Regimantas (Lietuvos matematikos rinkinys, 2008)
A fragment of a deterministic propositional dynamic logic (DPDL, in short) is considered The language of considered fragment contains propositional symbols, action constants, action operator (repetition) and logical symbols. For safety fragment of considered DPDL a loop-check-free sequent calculus with invertible rules is presented.